Estilos de aprendizagem no espaço virtual: um estudo com alunos dos cursos a distância da Universidade Federal do Maranhão – UFMA - MENDES, Ana Gardenia Lima Martins (2015)
This study of the research that you want to verify that before the current requirements of educational paradigms, the Degree courses in Pedagogy, Biology and Mathematics and Bachelor courses in Business Administration and Public Administration, in the distance, from the Federal University of Maranhão - UFMA They have worked in order to use the resources and tools made available by ICT from the perspective of learning styles and know the learning style and the virtual space of Use style prevalent among students of these courses. The methodology makes up into a quantitative research, including a sample of 206 students (68%) of the five courses, analyzed through a study of exploratory and descriptive case using the quea questionnaire Honey and Alonso (2002) on learning styles and the questionnaire Virtual Space Use Style (BARROS, 2011), as well as adaptation five questions prepared by the author. Through the results it was possible to identify the Reflective Style as the predominant learning style among all analyzed courses and EUBPEV - Style of Use Search and Research in Virtual Space (Reflective) predominantly to the Virtual Space Use Style. Of the five courses, most students said, already have some prior knowledge of the two theories, except for the Degree in Biology; never previously analyzed the predominant learning style, and; considers that the resources used for the courses which can involve participating in various learning styles. It was concluded that with this information on learning styles, we can get directions, perceptions and ways that allow recognize the peculiarities and preferences of the individuals involved, and so significant design strategies to be used in everyday school life.